OP11 ATYPICAL MENINGIOMA: IS ADJUVANT RADIOTHERAPY NECESSARY? - Waqar, Mueez (Oxford University Press, 2014)
INTRODUCTION: WHO grade II meningiomas have a greater propensity to recur than benign meningioma and the benefits of adjuvant radiotherapy are unclear. Existing studies report conflicting results. This study evaluated the role of early adjuvant radiotherapy following gross total resection of atypical meningioma. METHOD: Triple centre case-note review of adults with WHO grade II meningioma (2007 classification) diagnosed between 2001-2010. Multiple meningioma, NF2 and radiotherapy-induced meningioma were excluded. Extent of resection was defined as gross total resection (GTR: Simpson I-III) or subtotal resection (STR: Simpson IV-V). Survival analysis was performed using the Kaplan-Meier method. RESULTS: 136 patients were identified; median age 62 years (22-86) and median follow-up 57.3 months (0.1-152.2). Tumours were mostly located in the convexity (50.0%) or falcine/parasagittal regions (27.2%). Institutional differences in overall survival (OS) (log-rank = 1.33, p = 0.514) and progression-free survival (PFS) (log-rank = 0.478, p = 0.788) were not significant. GTR (achieved in 84.6%) was associated with longer PFS (5-year PFS 80.7% vs. 41.8%, log-rank = 9.334, p = 0.002) and a trend towards longer OS (5-year OS 76.1% vs. 40.4%, log-rank = 3.087, p = 0.079). After GTR, 29.6% received adjuvant radiotherapy, which did not improve OS (5-year OS 77% vs. 74%, Breslow's test = 0.312, p = 0.577) or PFS (5-year PFS 82 vs. 78%, Breslow's test = 0.804, p = 0.370). CONCLUSION: Extent of resection is an important prognostic variable. Adjuvant radiotherapy did not improve PFS or OS following gross total resection of atypical meningioma. Prospective randomized controlled trials are planned.